Association of Gastric Acid Suppression With Recurrent Clostridium difficile Infection: A Systematic Review and Meta-analysis - Tariq, Raseen (JAMA Intern Med, 2017)
IMPORTANCE: Gastric acid suppression has been associated with an increased risk of primary Clostridium difficile infection (CDI), but the risk of recurrent CDI in patients taking gastric acid suppressant medications is unclear. OBJECTIVE: To perform a systematic review and meta-analysis to evaluate the association between gastric acid suppressants and recurrent CDI. DATA SOURCES: MEDLINE, EMBASE, the Cochrane Central Register, the Cochrane Database, and Web of Science were searched from January 1, 1995, to September 30, 2015, for studies assessing the association between gastric acid suppressant exposure and recurrent CDI. Search terms included Clostridium difficile, pseudomembranous colitis, proton pump inhibitor, and histamine H(2 )blocker. STUDY SELECTION: Case-control studies, cohort studies, and clinical trials that included patients with CDI who did or did not receive gastric acid suppressant therapy and who were evaluated for recurrent CDI were included, with no restriction on study setting (inpatient or outpatient). DATA EXTRACTION AND SYNTHESIS: The Newcastle-Ottawa scale was used to assess the methodologic quality of included studies. In this scale, case-control and cohort studies were scored on selection, comparability, and ascertainment of the outcome of interest. Data were independently abstracted to a predetermined collection form by 2 investigators. Summary odds ratio estimates with 95% CIs were calculated using the random-effects model and software to calculate the pooled effect size of studies reporting multivariate analyses. MAIN OUTCOMES AND MEASURES: Risk of recurrent infection in patients with CDI and its association with use of gastric acid suppressant medication. RESULTS: Sixteen observational studies were included, together reporting 7703 patients with CDI; among these, 1525 patients (19.8%) developed recurrent CDI. The rate of recurrent CDI in patients with gastric acid suppression was 22.1% (892 of 4038 patients) compared with 17.3% (633 of 3665) in patients without gastric acid suppression, which indicated an increased risk by meta-analysis (odds ratio [OR], 1.52; 95% CI, 1.20-1.94; P < .001). There was significant heterogeneity among the studies, with an I(2) value of 64%. Subgroup analyses of studies adjusting for age and potential confounders confirmed an increased risk of recurrent CDI with use of gastric acid suppressants (OR, 1.38; 95% CI, 1.08-1.76; P = .02). CONCLUSIONS AND RELEVANCE: Meta-analyses of observational studies suggest that patients who receive gastric acid suppressants may be at increased risk for recurrent CDI. These data should be interpreted with caution because they may be confounded owing to the observational design of the individual studies. It may be reasonable to re-evaluate the need for these medications in patients with CDI.